Pengaruh Pendidikan Kesehatan Tentang Perawatan Pasien Stroke Di Rumah Terhadap Tingkat Pengetahuan Keluarga - Asrijal Bakri; Fransisco Irwandy; Elmiana Bongga Linggi (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Knowledge is everything that is known based on the results of sensing and experience gained by humans. Care of stroke patients at home by the family is all actions taken by the family in order to maintain the health of stroke sufferers, such as assisting in physical activities after a stroke, dealing with personal hygiene, dealing with eating and drinking problems, compliance with treatment programs at home. This study aims to determine the effect of health education about the care of stroke patients at home on the level of family knowledge. This type of research is a pre-experimental research, with the One Group Pre-test - Post-test Design approach. The population of this study is the families of stroke patients who are in the Neurology Polyclinic in Stella Maris Hospital Makassar. Sampling uses nonprobability sampling technique, with consecutive sampling approach. The number of samples of this study were 60 respondents and data collection was carried out using a questionnaire sheet. The statistical test used was the Wilcoxon test to determine the effect of health education about the care of stroke patients at home on the level of family knowledge and the value of p = 0,000 was obtained. Based on these statistical tests it is known that the value of p <α (0.05), it can be concluded that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, meaning that there is an influence of health education about the care of stroke patients at home on the level of family knowledge. Therefore, nurses are important to provide health education about the care of stroke patients at home to the family so that family knowledge is increasing.